Structure and magnetism of the topotactically reduced oxychloride Sr4Mn3O(6.5)Cl2. - Romero, F; Hayward, M (2012)
Reaction of the n = 3 Ruddlesden-Popper oxychloride Sr(4)Mn(3)O(7.5)Cl(2) with calcium hydride yields the topotactically reduced phase Sr(4)Mn(3)O(6.5)Cl(2). The deintercalation of oxide ions from the central MnO(1.5) layer of the starting phase is accompanied by a rearrangement of the anion lattice, resulting in a layer of composition MnO(0.5) in the reduced material, consisting of chains of MnO(4) tetrahedra connected by edge and corner sharing. Magnetization and low-temperature neutron diffraction data are consistent with antiferromagnetic coupling of manganese spins, but no long-range magnetic order is observed down to 5 K, presumably due to the large interlayer separation in the reduced phase. The influence of anion substitution on the structural selectivity of low-temperature reduction reactions is discussed.